Information Service and Entrepreneurial Skills Acquisition for the Students with Special Needs in Nigerian Secondary Schools - Olarewaju, Ogundele Michael Olarewaju; Simon Chalibiya (JIE, 2023)
The paper examined information service and entrepreneurial skills acquisition for the students with the special needs in Nigerian secondary schools. Since information provision for the citizens is power, information services for developing entrepreneurial skills acquisition in students with special needs is inevitable. It is therefore essential for the educational managers to provide all the necessary information services which assist the students with special need. The current expository study explained the concepts of information services, types of information, flow of information, causes of information blockage, needs for entrepreneurship skills acquisitions, methods of providing information services that will aid students with special needs to acquire necessary entrepreneurial skills to help them in their later life. Suggestions were made for the school managers to provide necessary information available for the career choices of students with special needs especially students of secondary schools.